2003
DOI: 10.1007/s00134-003-1734-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous recombinant human granulocyte colony-stimulating factor (filgrastim, rhG-CSF) on neutrophils of critically ill patients with systemic inflammatory response syndrome depend on endogenous G-CSF plasma concentrations on admission

Abstract: Besides activation of neutrophil maturation, low-dose rhG-CSF application in postoperative patients with SIRS has different effects on neutrophil functions, in part depending on already endogenously produced G-CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The use of granulocyte colony stimulating factor has also been used in patients with severe neutropenia. 22 A separate study from our institution which analyzed the survival outcomes of 106 patients with pseudomyxoma peritonei showed that severe morbidity has an adverse impact on survival. 23 The importance of this association must remind surgeons that a poor perioperative outcome, even if full recovery is established, may not translate to eventual long-term survival and that this can be rectified by being mindful of the associated risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The use of granulocyte colony stimulating factor has also been used in patients with severe neutropenia. 22 A separate study from our institution which analyzed the survival outcomes of 106 patients with pseudomyxoma peritonei showed that severe morbidity has an adverse impact on survival. 23 The importance of this association must remind surgeons that a poor perioperative outcome, even if full recovery is established, may not translate to eventual long-term survival and that this can be rectified by being mindful of the associated risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that age and gender have influence on immune functions, due to our limited possibilities we have included in our studies all patients with multiple trauma with ISS >15 and all patients with acute pancreatitis fulfilling the above exclusion criteria, regardless to age and gender (11,25,(27)(28)(29)(30)(31).…”
Section: Subject Selectionmentioning
confidence: 99%
“…4 G-CSF may also block the hyperinflammatory cytokine cascade mediated by inflammatory cytokines, such as tumor necrosis factor (TNF) and interleukin 1, before severe tissue damage occurs. 5 The timing of G-CSF administration may also affect patient outcomes. Unresolved infections may precipitate and drive the systemic inflammatory response, potentially resulting in multiple organ failure (MOF) and septic shock.…”
mentioning
confidence: 99%